Cytokinin elevation caused by high light intensity contributes substantially to the increase of thermotolerance of rice plants - Sylva Prerostova; Jana Jarošová; Petre Dobrev; Alena Gaudinova; Vojtech Knirsch; Eva Kobzova; Kinga Benczúr; Gabriella Szalai; Ondrej Novak; Radomira Vankova (Plant Stress)
Light is a crucial factor affecting plant development. Rice (Oryza sativa) responses to high light (HL, 1300 μmol m−2 s−1, 27 °C) were characterized. HL significantly elevated root-born cytokinin, trans-zeatin in leaves due to transpiration stream. Despite only minor changes in abscisic acid (ABA) and jasmonic acid (JA) levels, HL decreased expression of ABA biosynthetic gene NCED5, while promoted JA signalling pathway by down-regulated expression of repressor JAZ9. The maximum quantum yield of photosystem II (Fv/Fm) decreased, suggesting protection of photosystem II. HL stimulated sugar production, especially glucose and mannose. As modulation of cytokinin levels (applying exogenous cytokinin or inhibitors of their degradation) promoted rice thermotolerance, HL treatment causing cytokinin increase was tested on its potential positive effect on response to elevated temperature.The effects of heat stress (HS, 40 °C for 6 h) per se and in combination with HL were evaluated in leaves, crowns and roots. HS was applied to whole plants (HS-WP), or targeted to leaves (HS-L) or roots (HS-R). HS treatments down-regulated trans-zeatin levels. Simultaneous application of HL and HS to leaves (HL+HS-WP, HL+HS-L) reduced this impact. HL combined with HS affecting leaves also stimulated JA and auxin indole-3-acetic acid. Milder expression of HS-marker genes HSP90.2, HSP90.3, HSP26.2 and HSFA2d, and genes coding antioxidant enzymes (especially Fe-superoxide dismutase) indicated that HL increased rice thermotolerance. HL minimized strong negative effect of HS on sugars in roots. The data showed positive impacts of mid-term HL treatment on thermotolerance of rice, revealing a novel strategy for stimulation of plant defence.